2018
DOI: 10.1016/j.cmi.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin-guided antibiotic therapy in patients with fever in a general emergency department population: a multicentre non-inferiority randomized clinical trial (HiTEMP study)

Abstract: PCT-guided therapy was non-inferior in terms of safety, but did not reduce prescription of antibiotic regimens in an ED population with fever. In this heterogeneous population, the accuracy of PCT in diagnosing bacterial infections was poor. TRIAL REGISTRATION IN NETHERLANDS TRIAL REGISTER: http://www.trialregister.nl/trialreg/admin/rctview.asp?TC=4949.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 29 publications
0
52
1
Order By: Relevance
“…Third, the recently published HiTEMP study, investigated the value of PCT to guide antibiotic therapy in ED patients with fever in regard to rates of antibiotic prescription, clinical outcomes and costs [32]. Investigators did not find any added benefit of PCT, demonstrating that while PCT-guided therapy was non-inferior in terms of safety, it did not reduce the prescription of antibiotics.…”
Section: Learnings From 'Negative' Studiesmentioning
confidence: 99%
“…Third, the recently published HiTEMP study, investigated the value of PCT to guide antibiotic therapy in ED patients with fever in regard to rates of antibiotic prescription, clinical outcomes and costs [32]. Investigators did not find any added benefit of PCT, demonstrating that while PCT-guided therapy was non-inferior in terms of safety, it did not reduce the prescription of antibiotics.…”
Section: Learnings From 'Negative' Studiesmentioning
confidence: 99%
“…Interestingly, MR-proADM was also the most accurate parameter in identifying patients presenting to the ED or receiving treatment on a medical ward who subsequently required immediate ICU admission. The use of clinical or laboratory parameters which are significantly increased in the early stages of the infectious cascade may allow more appropriate treatment strategies to be initiated upon initial suspicion of infection, thus minimising the risk of patients being either underor over-treated-both of which may result in undesirable consequences [21]. To this extent, the use of blood biomarkers may provide an easy and rapid source of clinical information with which to inform and help develop clinical strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in serum CRP levels during the first 48 h after antibiotic initiation can help evaluate the response to initial antimicrobial therapy [27]. Likewise, a PCT-based algorithm may help reduce antibiotic exposure in septic patients without compromising clinical outcomes [28,29]. However, not all studies have shown the same positive effect [30], suggesting that the effectiveness of PCT-based algorithms may depend on the physician's experience and the clinical setting.…”
Section: Discussionmentioning
confidence: 99%